2024
DOI: 10.1021/acs.iecr.3c02619
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Bayesian Technique, Statistical Analysis, and the Maximum Adsorption Capacity in a Deterministic Way for Caffeine Removal by Adsorption: Kinetic and Isotherm Modeling

Júlia Toffoli de Oliveira,
Keila Guerra Pacheco Nunes,
Diego Cardoso Estumano
et al.

Abstract: The present work evaluates the Bayesian statistical method in adsorption, kinetic, and isotherm studies for estimation of the parameters along with the experimental data of the solid's maximum adsorption capacity. For the experimental data, the removal of caffeine (CAF) on granular activated carbon (GAC), previously characterized, was evaluated in five different temperatures (288, 298, 308, 313, and 323 K), and the following operational conditions were investigated: pH; adsorbent concentration (C GAC ), and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Moreover, the GAC pH PCZ value is 8.04, which suggests a positively charged solid surface at lower pH values; it can be concluded that the adsorbent is mostly alkaline, facilitating the adsorption of MBX. According to de Oliveira et al when the solution in contact with the adsorbent solid has pH < pH PCZ , the surface is positively charged, favoring the adsorption of anions; however, when the solution has pH > pH PCZ , the surface of the adsorbent is negatively charged. Consequently, the adsorption of cations is favored.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the GAC pH PCZ value is 8.04, which suggests a positively charged solid surface at lower pH values; it can be concluded that the adsorbent is mostly alkaline, facilitating the adsorption of MBX. According to de Oliveira et al when the solution in contact with the adsorbent solid has pH < pH PCZ , the surface is positively charged, favoring the adsorption of anions; however, when the solution has pH > pH PCZ , the surface of the adsorbent is negatively charged. Consequently, the adsorption of cations is favored.…”
Section: Resultsmentioning
confidence: 99%